2019
DOI: 10.1055/s-0039-1692647
|View full text |Cite
|
Sign up to set email alerts
|

Unicompartmental Knee Replacement Combined to Anterior Cruciate Ligament Reconstruction: Midterm Results

Abstract: A study was conducted to retrospectively evaluate the outcomes of combined medial unicompartmental knee replacement (UKR) and anterior cruciate ligament (ACL) reconstruction. The hypothesis was that this procedure would lead to satisfying results in patients affected by medial osteoarthritis and ACL insufficiency. Fourteen patients with ACL deficiency and concomitant medial compartment symptomatic osteoarthritis were treated from 2006 to 2010. Twelve of them were followed-up for an average time of 7.8 year (ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Of the seven included studies, two were prospective [ 17 , 18 ] and four were retrospective [ 19 , 20 , 21 , 22 ] of level of evidence (LOE) IV. One was a retrospective cohort study with comparison group of LOE III [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the seven included studies, two were prospective [ 17 , 18 ] and four were retrospective [ 19 , 20 , 21 , 22 ] of level of evidence (LOE) IV. One was a retrospective cohort study with comparison group of LOE III [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall number of combined procedures amounted to 169, with 169 patients involved. Within the included studies, the number of subjects varied from 8 [ 20 ] to 58 [ 17 ], with a mean age ranging from 44 [ 19 ] to 54 [ 21 ] years. The average follow-up was 6.3 years, ranging from 3.8 [ 22 ] to 14.6 [ 20 ] years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 16 During mid-flexion, the ACL and PCL provide knee joint stability, and during high flexion the PCL is responsible for posterior femoral rollback. 16 - 18 Ventura et al 19 showed that UKA combined with ACL reconstruction is an effective therapeutic option for the treatment of combined medial unicompartmental knee OA and ACL deficiency, and confirms subjective and objective clinical improvement up to eight years after surgery. However, long-term results suggest that an insufficient PCL may promote the development of OA in knee joints due to excessive displacements between the tibia and femur.…”
Section: Introductionmentioning
confidence: 84%